Mycobacterium avium subsp. paratuberculosis in cow bulk tank milk in Cyprus detected by culture and quantitative IS900 and F57 real-time PCR - Slana, I; Liapi, M; Moravkova, M; Kralova, A; Pavlik, I (Preventive veterinary medicine, 2009)
The possibility that Mycobacterium avium subsp. paratuberculosis (MAP) plays some role in the development of Crohn's disease in humans is attracting attention to milk and milk products originating from infected animals. In this study, we focused on the detection of MAP in 220 bulk tank milk (BTM) samples from all dairy cattle herds in Cyprus. In total, 63 (28.6%) BTM milk samples were found to be positive for MAP using quantitative real-time PCR assays for IS900 and F57. The presence of MAP in BTM was low, and was assessed to be several tens of MAP cells per one ml of BTM. Milk samples examined by cultivation were found to be negative for MAP in all 220 BTM. In two BTM samples cultivation and subsequent sequencing of 16S rRNA revealed two isolates of M. fortuitum.
Keywords: nemoci skotu; Sensitivity and Specificity; senzitivita a specificita; Humans; Paratuberculosis; Predictive Value of Tests; Female; RNA ribozomální 16S; bakteriální RNA; Mycobacterium avium subsp. paratuberculosis; lidé; zoonózy; zvířata; Colony Count, Microbial; RNA, Ribosomal, 16S; Řecko; ženské pohlaví; paratuberkulóza; Cattle; Cattle Diseases; Greece; Milk; prediktivní hodnota testů; kontaminace potravin; Food Contamination; počet mikrobiálních kolonií; polymerázová řetězová reakce; skot; Mass Screening; Polymerase Chain Reaction; Zoonoses; Animals; plošný screening; mléko; RNA, Bacterial